Experimental investigation on arsenic removal with a nanofiltration pilot plant from naturally contaminated groundwater - Saitua, Hugo Alberto (2011)
In this research, the efficiency and the arsenic removal mechanism with a Nanofiltration (NF) pilot plant from naturally contaminated groundwater have been evaluated. The process integral evaluation at 7bar shows an arsenate (HAsO42-) rejection over 95% and a total sulfate (SO42-) rejection. Divalent ions calcium and magnesium (Ca2+ and Mg2+) rejection produced an 81% reduction of the total hardness. The total dissolved solids TDS concentration decreased to 53%. Monovalent ions moderated rejections contributed to the membrane hydraulics stability. The arsenate (HAsO42-) rejection from an electrolytes solution (SO42-, HCO3-, F-, Cl-, NO3-, Ca2+, Mg2+, K+ and Na+) was prevalently ruled by Donnan exclusion combined with the preferential passage of more permeable ions. Results show the importance of ionic composition on ion transmission and rejection in the studied membrane. Ion rejection in multicomponent solutions showed to be significantly different to that in individual salt solutions. Whereas monovalent anion rejections remarkably decreased, divalent cation rejections were three times superior. In arsenate rejection (HAsO42-) from artificially contaminated natural groundwater, the membrane showed the same selectivity.